2011
DOI: 10.2139/ssrn.1978415
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of (Micro)Insurance in Southern Ghana: The Role of Information and Peer Effects

Abstract: This article investigates the understandings and perceptions of (micro)insurance among lowincome people in southern Ghana, using evidence from four focus group discussions. It analyzes how the focus group participants think about various types of insurance -among them a micro life insurance product -and how their negative and/or positive evaluations have come about. The evidence indicates that (micro)insurance is mostly positively perceived by the participants of the focus group discussions. However, it is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Insured fruit growers spend more than 29.5% (2SLS's estimation result) per Mu on chemical fertilizers and pesticides than uninsured farmers. The empirical result indicates that the inputexpense-increasing effect of COP insurance-meaning the marginal incentives to apply more input expense due to input expense being the main determinant for expected indemnity amounts-dominates the input-expense-decreasing effect of COP insurance that comes from the traditional moral hazard effect in yield-or revenue-based crop insurance [2,34]. Most previous studies, which investigated the effects of yield-or revenue-based crop insurance products on farmer input expense, showed that the traditional moral hazard effect of insurance plays a role in decreasing eventual input expense utilized by insured farmers [11][12][13]34,35].…”
Section: Discussion Of Core Explanatory Variablementioning
confidence: 99%
“…Insured fruit growers spend more than 29.5% (2SLS's estimation result) per Mu on chemical fertilizers and pesticides than uninsured farmers. The empirical result indicates that the inputexpense-increasing effect of COP insurance-meaning the marginal incentives to apply more input expense due to input expense being the main determinant for expected indemnity amounts-dominates the input-expense-decreasing effect of COP insurance that comes from the traditional moral hazard effect in yield-or revenue-based crop insurance [2,34]. Most previous studies, which investigated the effects of yield-or revenue-based crop insurance products on farmer input expense, showed that the traditional moral hazard effect of insurance plays a role in decreasing eventual input expense utilized by insured farmers [11][12][13]34,35].…”
Section: Discussion Of Core Explanatory Variablementioning
confidence: 99%
“…The uptake of microinsurance schemes by poor households, for example, depends to some extent on income levels but also on trust, familiarity with the product and the supplier, social networks and peer effects (Giesbert / Steiner 2011;Thornton et al 2010;Giné et al 2008;Anderson / Stamoulis 2006). A lack of trust in the provider or vendor of a productsuch as microinsurance or energy-related services -hampers its diffusion.…”
Section: Key Concepts Of Behavioural Economics In Energy Efficiencymentioning
confidence: 99%
“…To combat these risks, they have traditionally used risk pooling (for instance funeral and burial societies), income support (for instance credit arrangements and transfers) and informal insurance or risk-sharing schemes such as grain storage, savings, asset accumulation and loans from friends and relatives (Bhattamishra & Barrett, 2008;Tadesse & Brans, 2012). However, the prevalent forms of risk management (in kind savings, self-insurance, mutual insurance) which were appropriate earlier are no longer adequate and feasible (Pierro & Desai, 2007;Giesbert & Steiner, 2012) as they are limited in outreach and the benefits typically cover a small portion of the loss (Churchill, 2006), offer limited protection, low returns for households, and are prone to breakdown during emergencies (Bhattamishra & Barrett, 2008). Formal insurance instruments can offer superior risk management alternatives, provided poor households can access these services (Maleika & Kuriakose, 2008).…”
Section: Introductionmentioning
confidence: 99%